Andreia : studies in manliness and courage in classical antiquity - Rosen, Ralph Mark.; Sluiter, I. (Ineke) (Leiden ; Boston : Brill, 2003)
An examination of a central concept in the self-definition of any Greek-speaking male: "Andreia", the notion of courage and manliness. Through a combination of lexical or semantic and conceptual studies the discourse of manliness and its role in the construction of social order is explored
Semantics of manliness in ancient Greece / Karen Bassi -- Andreia of Xenocles / G.I.C. Robertson -- Marvelous Andreia / Sarah E. Harrell -- Andreia of the Hippocratic physician and the problem of incurables / Ralph M. Rosen and Manfred Horstmanshoff -- Most citizens are Europrôktoi now / Adriaan Rademaker -- Rhetoric of courage in the Athenian orators / Joseph Roisman -- High Cost of Andreia at Athens / Edward E. Cohen -- Ordeal of the divine sign / Peter T. Struck -- Aristotle on Andreia, divine and sub-human virtues / Marguerite Deslauriers -- Paradoxical Andreia / Helen Cullyer -- Roman men and Greek virtue / Myles McDonnell -- Andreia and the Askêsis-culture in the Roman East / Onno van Nijf -- Like the labors of Heracles / Joy Connolly -- Plutarch's manly women / Jeremy McInerney.
Includes bibliographical references and indexes.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Andreia (The Greek word); Classical literature -- History and criticism; Greek language -- Semantics; Masculinity -- Terminology; Civilization, Classical; Courage -- Terminology; Civilization, Ancient; Littérature ancienne -- Histoire et critique; Grec (Langue) -- Sémantique.; Masculinité -- Terminologie; Civilisation ancienne; Courage -- Terminologie; FOREIGN LANGUAGE STUDY -- Ancient Languages; Civilization, Ancient; Andreia (The Greek word); Civilization, Classical; Classical literature; Courage; Greek language -- Semantics; Masculinity; Männlichkeit; Griechenland; Mannelijkheid; Moed; Klassieke oudheid; Griechenland <Altertum>; Criticism, interpretation, etc; Terminology